Intensitas Serangan Penyakit Antraknosa yang Disebabkan Oleh Colletotrichum sp. pada Tanaman Cabai Rawit dan Cabai Besar di Desa Karya Maju Kecamatan Marabahan Kabupaten Barito Kuala - Nazwan Syah Bani Hasbi; Helda Orbani Rosa; Elly Liestiany (www.ulm.ac.id, 2021)
Anthracnose disease caused by Colletotrichum sp. is a disease that becomes one of the obstacles to production that causes large yield losses. Anthracnose is a disease that is difficult to eradicate because it can survive in the soil for quite a long time by spreading through splashes of water, air, agricultural equipment and others. This research aims to identify the intensity of anthracnose disease caused by Colletotrichum sp. This research procedure uses stratified purposive random sampling on fruit affected by anthracnose disease. The results of the calculation of the intensity of anthracnose disease in cayenne pepper are 48.29% and large chilies are 10.28%. Comparison of resistance levels of this variety is influenced by aspects of the pathogen, host plant and the environment.